EDUKASI PENGGUNAAN TABIR SURYA SEBAGAI UPAYA PENCEGAHAN KANKER KULIT PADA REMAJA DI PONDOK MODERN AL-KAUTSAR PEKANBARU - Arfina, Angga; Kharisna, Dendy; Yanti, Sri; Febtrina, Rizka; Azhar, Bayu; Hasanah, Ulfa (LPPM Institut Pendidikan Nusantara Global, 2024)
Skin cancer is one type of neoplasm that can be violent. One factor that can contribute to the occurrence of skin cancer is exposure to ultraviolet (UV) rays. Adolescents are an age group that has the potential to be exposed to UV rays longer and with high intensity. The use of sunscreen is recommended to prevent skin cancer due to UV exposure. The recommended use of sunscreens especially those containing SPF 30 or more. Providing education can increase knowledge and awareness in adolescents to prevent skin cancer and use sunscreen when outdoors. This community midwifery activity will be carried out in November 2023 at Pondok Modern Al-Kautsar Pekanbaru. The activity carried out was education to 30 teenagers about the use of sunscreen as an effort to prevent skin cancer. The activity was carried out first with a pre-test then continued with the presentation of material for 60 minutes and after that post test about skin cancer and the use of sunscreen. The results of activities in students and students there was an increase in skin cancer and the benefits of sunscreen in the prevention of skin cancer. It is expected for adolescents who will do outdoor activities to always use sunscreen according to recommendations to reduce the risk of skin cancer.